Analysis of foreign experience of development management of urban agglomerations - Chuvikina, Nataliya (Skhid, 2015)
Article is devoted to the foreign experience of development management of urban agglomerations. The work is characterized European and world agglomerations as major centers that are able to accumulate the economic potential of countries and increase their competitiveness. The differences in the development of urban agglomerations in the world and in Ukraine are determined by different vision of the main components of the system management of urban agglomerations. The management systems agglomerations in foreign countries are classified. The main four management models agglomerations abroad are identified. There are agglomeration in the form of public formation with one level of local government; agglomeration in the form of public formation "second tier" with preservation of the existing local government; "fragmented" or contracted agglomeration; agglomeration governed by regional authorities. Their negative and positive sides are revealed. The examples of European and international experience in regulating the development of agglomerations. On the basis of the identified features of models management of urban agglomerations abroad proposals for the construction of a national system of management of urban agglomerations are substantiated. It is concluded that the formation of Ukrainian management model agglomerations should be based on the implementation of the policy of a common organizational thinking, voluntary and parity of the parties involved in the process, diversity of forms of their interaction.